2011
DOI: 10.4061/2011/989438
|View full text |Cite
|
Sign up to set email alerts
|

Gene Duplication and the Genome Distribution of Sex-Biased Genes

Abstract: In species that have two sexes, a single genome encodes two morphs, as each sex can be thought of as a distinct morph. This means that the same set of genes are differentially expressed in the different sexes. Many questions emanate from this statement. What proportion of genes contributes to sexual dimorphism? How do they contribute to sexual dimorphism? How is sex-biased expression achieved? Which sex and what tissues contribute the most to sex-biased expression? Do sex-biased genes have the same evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 175 publications
(303 reference statements)
2
24
0
Order By: Relevance
“…More information about the nature of the master trigger for sex determination in X. borealis , on sex-linked genes, and on sex-biased expression of genes elsewhere in the genome may cast additional light on the drivers of sex chromosome turnover in these frogs. The drivers could include the role of alternative mechanisms that could resolve sexual conflict, such as gene duplication (Gallach et al 2011; Wyman et al 2012), which is a potentially important factor in these tetraploid species.…”
Section: Resultsmentioning
confidence: 99%
“…More information about the nature of the master trigger for sex determination in X. borealis , on sex-linked genes, and on sex-biased expression of genes elsewhere in the genome may cast additional light on the drivers of sex chromosome turnover in these frogs. The drivers could include the role of alternative mechanisms that could resolve sexual conflict, such as gene duplication (Gallach et al 2011; Wyman et al 2012), which is a potentially important factor in these tetraploid species.…”
Section: Resultsmentioning
confidence: 99%
“…As is seen with S. verreauxi , this male bias is often most pronounced in the testis [Meiklejohn et al, 2003;Ellegren and Parsch, 2007;Ingleby et al, 2014], with tissues such as the brain showing minimal sex bias [Ingleby et al, 2014]. It has been suggested that the phenomenon of male-biased expression is due to the rapid divergence and subsequent evolution of male genes in respect to both sequence and expression, ultimately owing to the fact that male genes are under less selective constraint [Ellegren and Parsch, 2007;Gallach et al, 2011;Parsch and Ellegren, 2013;Stuglik et al, 2014]. In Medaka (Oryzias latipes) the inhibitory action of the male sex determinant Dmrt1bY (DMY) supports the classical view that in at least XX/XY mechanisms, female sex determination appears to be the default pathway [Saito et al, 2007].…”
Section: Full Tissue Comparisonmentioning
confidence: 94%
“…In such cases, male and female genomes carry identical or almost identical DNA. It is possible that the subtle differences of a very small portion of genes located on sex-specific chromosomes or sex-determining region are responsible for the sex determination [20][22], and discovery of the Y-specific sequences may be difficult. In the extreme situation under this case like in the case of Fugu, there are no Y-specific sequences or Y-specific transcripts.…”
Section: Introductionmentioning
confidence: 99%